Lessons Learned from Facilitating a Pre-Service Teacher/Youth Mentoring Program - Alan English (The Advocate, 2019)
Traditional adult/youth mentoring programs have been associated with a host of positive academic, behavioral, and social/emotional youth outcomes. Little research, however, has been done on pre-service teacher/ youth mentoring programs; specifically if the benefits associated with more traditional mentoring programs translate into this context. For teacher educators, what is most promising about such mentoring programs is the potential for a mutually beneficial mentoring relationship. Pre-service teachers need experience working with youth as badly as youth need positive relationships and support. Furthermore, pre-service teachers need practicum experience throughout their coursework, at a time when some may not yet be ready to lead full classes in their content area. The author offers lessons learned after five semesters of facilitating a pre-service teacher/ middle school youth mentoring program as a case study in hopes to encourage such programs’ implementation into teacher education programs as well as research into such a program’s usefulness.
Keywords: Pre-service teacher; mentoring; youth; middle school